2014
DOI: 10.1016/j.elecom.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosive flexible pyrolytic polyimide graphite film as a cathode current collector in lithium bis(trifluoromethane sulfonyl) imide electrolyte

Abstract: a b s t r a c t a r t i c l e i n f oFlexible pyrolytic polyimide graphite film (PGF) is explored as a cathode current collector in lithium ion batteries using lithium bis(trifluoromethane sulfonyl) imide (LiTFSI) based electrolyte. It is demonstrated that no obvious anodic current is observed up to 4.5 V versus Li + /Li for PGF, while significant corrosion current is found from 3.6 V for aluminum, indicative of better electrochemical stability of PGF than that of aluminum in LiTFSI based electrolyte. LiMn 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Flexible polyimide graphite films possess a highly in-plane oriented structure [16], which endows the graphite film with excellent planar electrical conductivity and considerable mechanical strength. By laser drilling pores on the graphite films, more intercalation channels were obtained to improve the kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible polyimide graphite films possess a highly in-plane oriented structure [16], which endows the graphite film with excellent planar electrical conductivity and considerable mechanical strength. By laser drilling pores on the graphite films, more intercalation channels were obtained to improve the kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Aerward, LiMn 2 O 4 cathode active materials are grown on exible graphite current collector. 149 In addition, graphite lm with active materials possess extreme exibility that can be rolled up and could be altered into a variety of shapes as well as sizes enabling cell design exibility. Moreover, the cathode exhibits a high discharge capacity (135 mA h g À1 at 0.2C), and outstanding cycle life (89% capacity retentions aer 1000 cycles at 0.5C), and also retained 81% capacity over 300 cycles even when temperature raised up to 55 C. On the contrary, in the case of the aluminum-based current collector, the LMO/Al cathode is completely contaminated aer a few cycles.…”
Section: Graphite-supported Electrodesmentioning
confidence: 99%
“…16 Cui et al reported that with respect to pyrolytic graphite lm, Al current collector rapidly contaminated in lithium bis(triuoromethane sulfonyl)imide electrolyte containing system when temperature rises to 55 C. Also, PGF based electrode possesses a greater degree of exibility than that of Albased electrode. 149 From the abovementioned discussion, we can assume that carbonaceous materials are highly reliable for the fabrication of pliable and stable electrodes for FLIBs.…”
Section: Understanding Of Chemical and Configurational Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Some new lithium salts, such as LiTFSI, LiFAP, and LiBETI, with properties superior to those of LiPF 6 have been evaluated. 15,16 However, the new lithium salts due to some of their own drawbacks have not fully replaced LiPF 6 in LiMn 2 O 4 -based batteries in recent years.…”
Section: Introductionmentioning
confidence: 99%